Challenges in higher education: Differences between students with and without specific learning disorder and the moderating role of executive functions - Marlyn Khouri; Atheer Massarwe; Noga Cohen (PLoS ONE, 2025)
Students with Specific Learning Disorders (SLD) face difficulties not only in academic skills but also in the social, emotional, and executive function (EF) domains. These challenges may increase vulnerability to rumination—a repetitive and maladaptive focus on distress, which is strongly linked to emotional difficulties. This study explores differences in academic, social, emotional, and EF challenges between students with and without SLD and investigates whether these challenges moderate the relationship between SLD and rumination. A sample of 95 college students (46 with SLD, 49 without SLD) completed questionnaires assessing rumination and emotional distress. They also completed a writing task in which they provided an upsetting event related to their studies. The event were coded to four categories related to students’ challenges: academic, social, emotional, and EF challenges. Results indicated that students with SLD reported significantly higher levels of rumination, greater EF challenges, and higher levels of perceived stress than their peers. A moderation analysis further revealed that EF difficulties significantly moderated the link between SLD and rumination, with students experiencing both SLD and EF challenges showing the highest rumination levels. Findings emphasize the critical role of EF in the emotional experiences of students with SLD. Addressing EF deficits among students with SLD can reduce emotional distress and improve academic outcomes.